Metagenomic analysis of the gastric microbiota cultivable from a patient with gastritis concomitant with Barrett’s esophagus - Gutiérrez-Escobar, Andrés Julián (2017)
Barrett’s esophagus is a distal metaplasia characterized by the transformation of squamous mucosa into columnar mucosa. This esophageal phenotype is a product not only of the chronic reflux of gastric acids, but also by microorganisms that colonize the oral cavity and stomach. Two classes of microbiota can be identified in Barrett’s esophagus; microbiota type I is associated with the normal esophagus and type II with an inflamed esophagus. The present study describes the gastric microbiota of a patient with antral gastritis concomitant with Barrett’s esophagus absent infection with Helicobacter pylori. Gastric biopsies were obtained following the protocol of Sydney and following ethical practices. The isolates were cultivated under microaerophilic conditions on Columbia Agar supplemented with IsoVitaleX™ and 7% sterile blood. Extracted DNA was sequenced using 454-GS and the results analyzed on the MG-RAST server. Gram negative isolates were found and bacteria resistant to levofloxacin, amoxicillin, tetracycline, erythromycin, and clarithromycin. The phyla Bacteroidetes, Firmicutes, Fusobacteria and Proteobacteria, the genus Bacteroides and the species group Bacteroides fragilis were most abundant. Functionally, the metabolism of carbohydrates, amino acids, and to a lesser extent, the metabolism of cofactors and vitamins were most dominant, and of which the enzymes β-glucosidase (EC 3.2.1.21), β-galactosidase (EC 3.2.1.23) and β-N-acetylhexosaminidase (EC 3.2.1.52) were most dominant. The findings of this study, because they are of only one case may probably suggest a possible pathogenic role, previously undescribed for Bacteroides fragilis, associated with human gastritis when concomitant esophageal pathology exists.